Experiences of Adults Who Identify as Primary Caregivers. Issue 1 (10th April 2018) - Bordonada, Tiffany M.; Feather, Katherine A.; Ohrt, Jonathan H.; Waddington, Ashley F.
Abstract : The role of primary caregiver is unique. Understanding the role of the primary caregiver will better inform those in the counseling profession. The purpose of this qualitative research study was to gain a clearer perspective of the lived experiences of adults who identify as primary caregivers. The authors conducted semistructured interviews with 6 Caucasian female participants and analyzed the data using interpretative phenomenological analysis. The findings include personal perceptions and caregiver experiences pertaining to the caregiver role, caregiver mentality, professional identity, social and emotional responses, and self‐care among caregivers throughout the caregiving process. Implications for counselors and future research are presented.